Carbonation deep evaluation of a concrete structure subjected to fire soot - Carneiro Valério, Allan; Roberto do Lago Helene, Paulo (Revista ALCONPAT, 2025)
The objective of this study was to verify the influence of moderate heat (< 200ºC) and soot from fires on the alteration of carbonation of concrete. Although this fact occurs naturally in all small and large fires, these authors did not find bibliographic references on the subject. An experiment of exposing concrete specimens to moderate temperatures was then performed, followed by soot impregnation for twelve months, with the measurement of carbonation depth every three months. The study was carried out in a laboratory environment and compared the depth of carbonation observed in specimens subjected to moderate temperatures and soot with specimens under laboratory environmental conditions. Despite the natural limitations of an experiment with a reduced time frame and laboratory environment, it was evidenced that even in intact concretes, the moderate temperatures combined with the acidity of the soot accelerate the carbonation depths and can significantly alter the residual service life of the structure if subsequent corrective intervention measures do not consider this risk.